2019
DOI: 10.1063/1.5085666
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bed proximity on the three-dimensional characteristics of the wake of a sharp-edged bluff body

Abstract: The gap flow effect in a wake is investigated to develop an improved picture of the formation of fluid structures via a numerical simulation of flow past a bluff body with two different clearances from the bed. These two cases are compared with the no-gap case which is considered as a reference case. The transient three-dimensional Navier-Stokes equations are numerically solved using a finite volume approach with the detached eddy simulation as the turbulence model. The effect of the free surface is included i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Furthermore, successive grids were compared to determine whether or not there was a change in the mean characteristics. The results for the mean flow quantities and cell independence study were very similar to those reported earlier in [8], [21], [22] and are not repeated here for brevity. In this study, the total number of cells used for the computation is 1.3 and 8.7 million elements for AR = 1 and 12, respectively.…”
Section: Mesh Generationsupporting
confidence: 83%
“…Furthermore, successive grids were compared to determine whether or not there was a change in the mean characteristics. The results for the mean flow quantities and cell independence study were very similar to those reported earlier in [8], [21], [22] and are not repeated here for brevity. In this study, the total number of cells used for the computation is 1.3 and 8.7 million elements for AR = 1 and 12, respectively.…”
Section: Mesh Generationsupporting
confidence: 83%
“…A distinguished structure at the near-bed location is generated when the gap is introduced in the wake flow. The extent and strength of this structure increase with the increase of the size of the gap [7]. The interaction between this structure and the other fluid structures boosts the vertical velocity component that is normal to the bed.…”
Section: Introductionmentioning
confidence: 96%
“…This type of flow is often encountered in engineering applications, e.g., the airflow around solar panels, flow around vehicles, and the cooling of electronic components. Many experimental and computational studies have been carried out with sharp-edged plate, circular and square cylinders as a bluff body to investigate the influence of the gap size on the wake characteristics, such as works of Shinneeb and Balachandar [1], Shinneeb et al, [2], Martinuzzi et al, [3], Bosch et al, [4], Essel et al, [5] and Nasif et al, [6,7]. In these studies, the bluff bodies were oriented horizontally and vertically at different heights above the bed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aerodynamics and aeroacoustics of standard bluff bodies are subject of considerable interest owing to their widespread applications in science and engineering. [1][2][3][4][5][6][7][8] For example, during vehicle design and development stages, evaluating the noise generated due to the wind and its propagation into the cabin becomes critical as the wind-induced noise is a dominant noise source at speeds greater than 100 km/h. Frequent exposure to wind-induced noise can lead to driver fatigue, which for longer journeys may impact driver's safety at high noise levels, whereas, at lower levels of noise, it can impact the degree of vehicle refinement.…”
Section: Introductionmentioning
confidence: 99%